PROBLEMATIK PENERAPAN UNDANG-UNDANG HAK KEKAYAAN INTELEKTUAL TENTANG INDIKASI GEOGRAFIK PADA UNDANG-UNDANG MEREK - Sanjaya, Umar Haris (Jurnal Panorama Hukum, 2016)
Implementation of Act Nomor 15 Year 2001 already happened since 2001 in Indonesia. This regulation is adopted from TRIPs International Convention (Trade Related Aspects of Intellectual Property Rights) which have ratified by Indonesia. One of the substantion on it is merk protection of intellectual property.Ã‚Â  Nowday, every district in Indonesia has it product related the natural resources. This product is becoming the symbol of market from each district in Indonesia. Its become a symbol market of district because of every district has a special characteristic. This characteristic is called geographic indication according to act Number 15 year 2001 about merk. Later on formulation of geographic indication in Act Number 15 year 2001 potentially come a problematic in the purposes and characteristic. Its because of nature of geographic indication is different within merk according act Number 15 year 2001 generally.